Społeczne niebezpieczeństwo czynu jako warunek kryminalizacji - Kulesza, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
A human action in order to be criminalized must be deemed socially harmful. In the social realm it is necessary to identify an action perceived as potentially harmful to legally protected values, that is one infringing upon them or threatening them to a degree exceeding socially accepted limits, one that is required or expected to be criminalized. The social threat as a particular characteristic of a human action serves as the broadest justification hence a verification and a rationalization of a criminal prohibition. The presumed abstract social harm a threat of an action which is to be criminalized serves as the lawmaker’s prerequisite for criminalization. Its constitutional foundations lie in the principles of a democratic state and the consecutive principle of proportionality is perceived broadly as a guarantee against the criminalization of actions that do not pose a social threat or ones that exercise individual rights and freedoms granted within the constitution. Penalizing actions that pose no social threat is a violation of the constitution. The notion of a social threat plays therefore a dual role. It obliges t he lawmaker to act in cases when the threat to individual rights and freedoms exceeds the socially acceptable level, including the obligation to introduce criminal measures against any particularly harmful infringement of those rights, but also the need to intervene in order to protect the values shared within a society. In the latter case the potential criminalization is originated within the principles and values expressed in Articles 2 and 5 of the Polish constitution. On the other hand, the potential social harm of an action serves as a safeguard against a too far reaching legal interference in individual rights and freedoms. This purpose is expressed in Article 31 para. 3 of the constitution. This limitative clause is to warrant the right balance between the protection of individual rights and freedoms or the protection of shared social values and state interference in those individual rights and freedoms necessary to ensure such protection.
Keywords: społeczne niebezpieczeństwo czynu; materialny element przestępstwa; odpowiedzialność karna; konstytucyjny zakres kryminalizacji